Rap1 and mTOR signaling pathways drive opposing immunotoxic effects of structurally similar aryl-OPFRs, TPHP and TOCP - Bilin Zhao; Shuang Zheng; Gaoxiang Yang; Zhijun He; Jiewei Deng; Lijuan Luo; Xinyan Li; Tiangang Luan (Environment International)
Aryl organophosphorus flame retardants (aryl-OPFRs), commonly used product additives with close ties to daily life, have been regrettably characterized by multiple well-defined toxicity risks. Triphenyl phosphate (TPHP) and tri-o-cresyl phosphate (TOCP), two structurally similar aryl-OPFRs, were observed in our previous study to exhibit contrasting immunotoxic effects on THP-1 macrophages, yet the underlying mechanisms remain unclear. This study sought to address the knowledge gap by integrating transcriptomic and metabolomic analyses to elucidate the intricate mechanisms. During individual omics analyses, we unfortunately only obtained highly similar results for both TPHP and TOCP, failing to identify the key reasons for their differences. These results revealed comparable disturbances induced by both compounds, including disruptions in nucleic acid synthesis and energy metabolism, blocking ADP to ATP conversion by reducing TCA cycle intermediates, consequently leading to ATP depletion. However, through integrative analysis, specific pathways affected by each compound were successfully identified, shedding light on their unique effects. TPHP reduced GTP levels necessary for Rap1 activation, thereby inhibiting phagocytosis and adhesion of THP-1 macrophages. Conversely, TOCP stimulated the mTOR signaling pathway, enhancing phosphorylation of downstream proteins S6K, RHOA, and PKC, consequently promoting immune responses. This study not only clarified the distinct immunotoxic mechanisms of TPHP and TOCP but also provided critical insights into how structural variations in aryl-OPFRs can lead to markedly different immune responses, thereby informing future risk assessments and regulatory strategies for these compounds.